The effect of simple heat treatment on apatite formation on grit‐blasted/acid‐etched dental Ti implants already in clinical use. Issue 2 (29th July 2021) - Ogura, Ayano; Yamaguchi, Seiji; Le, Phuc Thi Minh; Yamamoto, Kayoko; Omori, Michi; Inoue, Kazuya; Kato‐Kogoe, Nahoko; Nakajima, Yoichiro; Nakano, Hiroyuki; Ueno, Takaaki; Yamada, Tomohiro; Mori, Yoshihide
Abstract: Grit‐blasted/acid‐etched titanium dental implants have a moderately roughened surface that is suitable for cell adhesion and exhibits faster osseointegration. However, the roughened surface does not always maintain stable fixation over a long period. In this study, a simple heat treatment at 600°C was performed on a commercially available dental Ti implant with grit‐blasting/acid‐etching, and its effect on mineralization capacity was assessed by examining apatite formation in a simulated body fluid (SBF). The as‐purchased implant displayed a moderately roughened surface at the micrometer scale. Its surface was composed of titanium hydride accompanied by a small amount of alumina particles derived from the grit‐blasting. Heat treatment transformed the titanium hydride into rutile without evidently changing the surface morphology. The immersion in SBF revealed that apatite formed on the heated implant at 7 days. Furthermore, apatite formed on the Ti rod surface within 1 day when the metal was subjected to acid and heat treatment without blasting. These indicate that apatite formation was conferred on the commercially available dental implant by simple heat treatment, although its induction period was slightly affected by alumina particles remaining on the implant surface. The heat‐treated implant should achieve stronger and more stable bone bonding due to its apatite formation.